Development of a European Human Embryonic Stem Cell Registry. (November 2008) - Borstlap, J; Kurtz, A; Stacey, G; Elstner, A; Damaschun, A; Aráán, B; Gerlach, JC; Izpisúúa, JC; Veiga, A
The number of human embryonic stem cell (hESC) lines that are available and that are subsequently being used in numerous research projects is increasing steadily. However, there is little coordination of hESC line derivation, and comparative information on the characteristics and quality of these cells is sparse. Obtaining consistent information on hESCs is hampered further by legislative fragmentation, particularly in Europe. Recognizing these obstacles, the European Commission has set up a Human Embryonic Stem Cell Registry (hESCreg) to make hESCs and their characterizing information accessible and to ensure that the results of research become more quickly available to the public. The primary objectives of hESCreg are to provide freely accessible information on existing hESC lines, their derivation, molecular characteristics, use and quality. Successful research with listed hESC lines will be used to evaluate clinical potential and thus directly influence policy decisions. The developing integration with other initiatives, such as characterization projects, registries and cell banks, is expected to lead to a common and internationally accepted central reference. The hESCreg provides a first step in this direction and might grow into an internationally funded and administered project.